LAW ENFORCEMENT ON THE INHERITANCE OF SIRI MARRIED IN THE JUDICIAL VERDICT - Rusli Rusli; Nur Mohamad Kasim; Duke Arie Widagdo (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2020)
Siri marriage is an interesting issue to be discussed in various perspectives. The legal consequences of unmarried marriage need clarity, especially in terms of inheritance rights. The law Number 1 of 1974 concerning marriage has required that marriages be recorded, as a form of legality recognized by the State. But on the other hand, the Marriage Law has provided absolute freedom to get married in accordance with the provisions of their respective religions. In various legal products, through law enforcement in the judiciary, it creates many perspectives, resulting in multiple interpretations in the position of the right of inheritance in siri marriage. This research, more specifically, examines law enforcement against siri marriage by examining judicial verdicts. The research approach focuses more on normative law by focusing on the study of legal norms, in producing new arguments, theories or concepts. The research data were collected through a library review and legal opinion. The findings of this study indicate that law enforcement of the inheritance rights of siri marriage gets a portion of the inheritance by substantially considering the aspects of justice. Judicial decisions consider aspects of legal benefit to the rights arising from unmarried marriage. The implication of this finding is that the marriage law is urgent to be amended, the occurrence of multiple interpretations of legal marriage becomes a gap in the implementation of unregistered marriage.Keywords: Law Enforcement, Siri Marriage, Judge’s Verdicts.